The Role of Lecturer and Student Human Resource Management in Improving Educational Quality: A Case Study of an Early Childhood Education Program - Widyatmike Gede Mulawarman; Eka Selvi Handayani; Apriliyani Apriliyani; Hamidah Hamidah; Yuli Wulandari (FKIP - Universitas Riau, 2026)
This study aims to examine the role of human resource management (HRM) of lecturers and students in improving educational quality at the Early Childhood Education (PAUD) Study Program, Faculty of Teacher Training and Education, Universitas Widya Gama Mahakam Samarinda. Educational quality in higher education is strongly influenced by the effectiveness of human resource management, particularly lecturers as key actors in learning and students as active participants in academic processes. This research employed a qualitative descriptive approach using semi-structured interviews with the head of the study program, lecturers, and students. Data were analyzed inductively through data reduction, coding, categorization, and thematic interpretation. The findings reveal that lecturer HRM plays a crucial role in maintaining instructional quality; however, challenges arise due to lecturers’ limited time availability caused by professional commitments outside the institution. In addition, most students are working students who experience difficulties in managing study time, which affects academic performance and timely graduation. Flexible academic scheduling, structured seminar planning, and strengthened academic guidance were identified as effective strategies to enhance educational quality. This study concludes that adaptive and sustainable HRM practices for both lecturers and students are essential to support continuous improvement of educational quality in higher education.